2016
DOI: 10.1007/s11467-016-0567-4
|View full text |Cite
|
Sign up to set email alerts
|

Survey of plasmonic gaps tuned at sub-nanometer scale in self-assembled arrays

Abstract: Creating nanoscale and sub-nanometer gaps between noble metal nanoparticles is critical for the applications of plasmonics and nanophotonics. To realize simultaneous attainments of both the optical spectrum and the gap size, the ability to tune these nanoscale gaps at the sub-nanometer scale is particularly desirable. Many nanofabrication methodologies, including electron beam lithography, self-assembly, and focused ion beams, have been tested for creating nanoscale gaps that can deliver significant field enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Metallic NP films are also known as nanogap-controlled plasmonic structures. The optical properties of metallic NP films are influenced by the physical and chemical control of interparticle gaps. , Several studies have reported the fabrication of plasmonic strain sensors using metallic NP films, , which can detect mechanical deformations based on strain-induced optical changes in interparticle gaps. However, the operating mechanism of the proposed plasmonic strain sensor differs from that of conventional metallic NP films.…”
Section: Introductionmentioning
confidence: 99%
“…Metallic NP films are also known as nanogap-controlled plasmonic structures. The optical properties of metallic NP films are influenced by the physical and chemical control of interparticle gaps. , Several studies have reported the fabrication of plasmonic strain sensors using metallic NP films, , which can detect mechanical deformations based on strain-induced optical changes in interparticle gaps. However, the operating mechanism of the proposed plasmonic strain sensor differs from that of conventional metallic NP films.…”
Section: Introductionmentioning
confidence: 99%